-(7x+9y+5)=

Simple and best practice solution for -(7x+9y+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7x+9y+5)= equation:


Simplifying
-1(7x + 9y + 5) = 0

Reorder the terms:
-1(5 + 7x + 9y) = 0
(5 * -1 + 7x * -1 + 9y * -1) = 0
(-5 + -7x + -9y) = 0

Solving
-5 + -7x + -9y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + -7x + 5 + -9y = 0 + 5

Reorder the terms:
-5 + 5 + -7x + -9y = 0 + 5

Combine like terms: -5 + 5 = 0
0 + -7x + -9y = 0 + 5
-7x + -9y = 0 + 5

Combine like terms: 0 + 5 = 5
-7x + -9y = 5

Add '9y' to each side of the equation.
-7x + -9y + 9y = 5 + 9y

Combine like terms: -9y + 9y = 0
-7x + 0 = 5 + 9y
-7x = 5 + 9y

Divide each side by '-7'.
x = -0.7142857143 + -1.285714286y

Simplifying
x = -0.7142857143 + -1.285714286y

See similar equations:

| (2x^2)-5x=33 | | sinx=-0.4x+1.2 | | (2x^2)-(5x)=33 | | 9*10x=17 | | y^2+2y+4=5ty^2 | | 2x+12y=-22 | | 2(3)-6=-3y | | ln(x)=56 | | 1.5y-x=-6 | | -18+9r-6r+4= | | 0=x^5+5x^4-2x^3-24x^2 | | y=4x^2+10x-4 | | 36+5t=-12-3t | | 5n-8=4n+2n | | g(c+1)=x+4 | | 2(x+3)+3x=-3(x-2)+8x | | 9.2x-18.4=8.9x-53.4 | | f(x)=6x^2+78 | | -72x=20x+92 | | 26=-68x+42x | | 6v^2-11v-35=0 | | 3a-4b+c-d=0 | | ln(x+6)+ln(x+5)=ln(5) | | f(x)=2x^4-x^3+49x^2-25x-25 | | n-1.4n-1=6(n-2.3) | | C-32=71 | | x+(x+40)=110 | | 2ln(lnx)-ln(5lnx-6)=0 | | a-6.6=10.1 | | -17x+2(x+14)=-2 | | y^2=x^2-x^4 | | (X^8)-1=0 |

Equations solver categories